The Synthesis Of Polycarboxylate Ether Polymers For Use As Additive In Ternary Blended Concrete - Ng, Peck Gee (2019)
Ground granulated blast furnace slag–pulverized fly ash (GGBS-PFA) cement concrete is widely used in the contemporary concrete industry. But both GGBS and PFA are incompatible with polycarboxylate (PCE) polymers as reported in previous studies. It can be seen by the segregation effect and bleeding of ternary blended cement concrete containing PCE in its fresh state. As such, the ratio of α- methoxy-ω-hydroxy-poly(ethylene glycol) (M-PEG) to methacrylic acid (MAA) was adjusted to reduce the water demand of the GGBS-PFA ternary blended cement concrete while maintaining favorable segregation and bleeding resistance. This study was conducted to investigate the effect of PCE polymers with varying main chain densities (M-PEG) and side chain densities (MAA) on fresh and hardened of GGBSPFA ternary blended cementitious composite properties. A total of five PCE polymers were designed and synthesized with various main chain densities (M-PEG) and side chain densities (MAA) for use in concrete fabrication. Before concrete fabrication, the mix design parameters for the concrete fabrication were optimized with respect to binder compositions, ratio of coarse aggregates to fine aggregates (CA/FA), PCE polymers dosage and the designed water-binder (w/b) ratio. The fabricated concrete was tested in terms of workability, strength development and durability performance while the properties of the GGBS-PFA cement paste with the synthesized PCE were accessed. Furthermore, an analysis of PCE polymer characteristics was carried out using Fourier Transform Infrared Spectroscopy (FTIR) and Nuclear Magnetic Resonance (NMR).